The Effect of teacher empowerment on job satisfaction - Tamim, Maya J (Beirut Lebanese American University- School of Arts and Sciences - Department of Education., 2006)
The growing number of research in school leadership is calling for a move from autocratic top-down leadership to a more democratic leadership style based on shared responsibility, increased teacher autonomy, and higher collaboration and teamwork to enhance professional growth and insure teacher commitment and satisfaction. This case study was conducted in a school in Beirut to examine an empowering leadership style in practice and find out what is its effect on teacher satisfaction. It addresses the issue of empowerment by integrating theory and practice using field-based data. Participants were twelve teachers chosen from the elementary, intermediate, and secondary divisions, the principals of each school division, and 2 subject coordinators. Interviews with all participants and a questionnaire addressing a sample of 154 teachers were used to collect data. Results showed that the school adopts an empowering leadership philosophy which is positively affecting the school climate and resulting in teacher satisfaction.
: Mémoire
Keywords: Job Satisfaction; Satisfaction professionnelle